The Effect of Achievement Motivation on Organizational Commitment in High School Level of Education - Nurochim, Nurochim (TARBIYA: Journal of Education in Muslim Society, 2020)
AbstractThis article aims to discuss the effect of economic civil servant teachers' achievement motivation to the organizational commitment in Jakarta High Schools. All this time, Commitment is always associated with motivation. Organisational commitment is a picture of an individual who identifies with the organisation and has a common goal. Organisational commitment does not come by itself but is influenced by factors such as motivation. Therefore, it becomes vital to examine further the effect of motivation, in this case, the achievement motivation of teachers concerning organisational commitment. This study applied quantitative research design with survey methods while employing a path analysis model to analyse the data. A total of 200 economic teachers from the Municipality of East Jakarta, Central Jakarta, West Jakarta, South Jakarta, and the Thousand Islands District joined this study. Sampling in this study was chosen by (simple random sampling) of the population. This study found that based on the results of the analysis and testing of the hypothesis, it can be found that achievement motivation has given a direct positive effect to organizational commitment. Based on this empirical evidence, it can be seen that this finding shows that achievement motivation is one of the variables that have a direct positive effect on organisational commitment.   AbstrakArtikel ini bertujuan untuk membahas pengaruh motivasi berprestasi guru PNS bidang ekonomi terhadap komitmen organisasi di SMA Negeri Jakarta. Selama ini Komitmen selalu dikaitkan dengan motivasi. Komitmen organisasi merupakan gambaran individu yang mengidentifikasikan diri dengan organisasi dan memiliki tujuan yang sama. Komitmen organisasi tidak datang dengan sendirinya tetapi dipengaruhi oleh faktor-faktor seperti motivasi. Oleh karena itu, menjadi penting untuk mengkaji lebih jauh pengaruh motivasi dalam hal ini prestasi belajar guru terhadap komitmen organisasi. Penelitian ini menggunakan desain penelitian kuantitatif dengan metode survei dengan menggunakan model analisis jalur untuk menganalisis data. Studi ini diikuti oleh 200 guru ekonomi dari Kota Jakarta Timur, Jakarta Pusat, Jakarta Barat, Jakarta Selatan, dan Kabupaten Kepulauan Seribu. Pengambilan sampel dalam penelitian ini dipilih dengan (simple random sampling) dari populasi. Penelitian ini menemukan bahwa berdasarkan hasil analisis dan pengujian hipotesis diketahui bahwa motivasi berprestasi berpengaruh langsung positif terhadap komitmen organisasi. Berdasarkan bukti empiris tersebut dapat diketahui bahwa temuan ini menunjukkan bahwa motivasi berprestasi merupakan salah satu variabel yang berpengaruh langsung positif terhadap komitmen organisasi.  How to Cite:  Nurochim (2020).  The Effect of Achievement Motivation on Organizational Commitment in High School Level Of Education. TARBIYA: Journal of Education in Muslim Society, 7(2), 192-203. doi:10.15408/tjems.v7i2.15956.